Stability of goji bioactives during extrusion cooking process. (1st September 2017) - Kosińska-Cagnazzo, Agnieszka; Bocquel, Dimitri; Marmillod, Isabelle; Andlauer, Wilfried
Highlights: Goji addition enhances antioxidant activity and bioactive content of extrudates. Incorporation of fruits into extrudates affect colour of final product. Antioxidant activity of extrudates increases with increasing extrusion temperature. Extruded cereals with goji berries are a good source of zeaxanthin dipalmitate. The vitamin C analog 2-O-β-d -glucopyranosyl-l -ascorbic acid shows excellent extrusion stability. Abstract: Due to the increasing popularity of goji berries, efforts are made to enlarge the offer of goji containing foods. In this study, rice flour based extrudates enriched with goji berries were investigated. The extrusion was performed using a twin screw extruder with constant feed moisture and screw speed. Raw mixtures as well as extruded products obtained were analysed in order to determine antioxidant activity and contents of rutin, zeaxanthin dipalmitate and 2-O-β-d -glucopyranosyl-l -ascorbic acid. The antioxidant activity of goji extrudates was boosted up to 20 times compared to the extrudates without any addition. The process of extrusion increased the antioxidant activity despite of decrease in rutin content. Regardless of extrusion conditions rutin retention in the extrudates was not lower than 60% compared to the respective raw mixtures. In the case of zeaxanthin dipalmitate the retention level was around 40%. 2-O-β-d -glucopyranosyl-l -ascorbic acid was stable at the conditions applied.